AJARAN ISLAM MENGAJARKAN PEMBENTUKAN KARAKTER MULIA : MENGEKSPLORASI PERANNYA DALAM PENANAMAN AKHLAK TERPUJI - Iswantono, Helbi; Yulianti, Dwi; Hafidhah, Nur; Shanata, Maura; Alawi, Muammar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Building Noble Character: The Role of Islam in Moral Formation explores the important role of Islamic education in shaping the moral character of individuals. The article explores the importance of Islamic teachings in guiding individuals towards a life of morality and integrity. It discusses the importance of Islamic values in fostering a sense of responsibility, compassion and self-discipline, in order to build a strong moral foundation. The research examines the impact of Islamic education on moral character development, focusing on the role of Islamic teachings in promoting values such as honesty, kindness and respect for others. The findings suggest that Islamic education plays an important role in shaping the moral character of individuals, especially in the context of contemporary society where moral values are often challenged. The study concludes that Islamic education is essential for fostering a sense of moral responsibility and promoting a culture of virtue, which ultimately contributes to the development of a more compassionate and just society.